2014
DOI: 10.5539/ijef.v6n3p64
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomic Determinants of Stock Market Development in Selected European Countries: Dynamic Panel Data Analysis

Abstract: This paper is concerned with the effects of macroeconomic variables and their role in development of stock market in selected Europen countries by estimating a dynamic panel data for the period of 1995-2011. We found that income, monetazation ratio, liquidity ratio, saving rate and inflation effect on stock market development. Monetazation ratio and inflation have negative effects while income, liquidity ratio, saving rate have positive effects on stock market development. Liquidity ratio emphasizes that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The continuous growth in economic activities lowered the fixed cost of stock market formation, thereby encouraging more investors to participate in the stock market. This finding is consistent with most of the studies which document a positive association between stock market development and economic growth (Atje and Jovanovic, 1993;Zervos, 1996, 1998;Cherif and Gazdar, 2010;S ükrüo glu and Nalin, 2014;Raza et at., 2015;Bayar, 2016;Ho, 2019). In terms of trade openness, the results show that a percentage increase in trade openness promotes stock market development by approximately 2.513 per cent.…”
Section: Empirical Analysis Using Autoregressive Distributed Lag Boun...supporting
confidence: 91%
“…The continuous growth in economic activities lowered the fixed cost of stock market formation, thereby encouraging more investors to participate in the stock market. This finding is consistent with most of the studies which document a positive association between stock market development and economic growth (Atje and Jovanovic, 1993;Zervos, 1996, 1998;Cherif and Gazdar, 2010;S ükrüo glu and Nalin, 2014;Raza et at., 2015;Bayar, 2016;Ho, 2019). In terms of trade openness, the results show that a percentage increase in trade openness promotes stock market development by approximately 2.513 per cent.…”
Section: Empirical Analysis Using Autoregressive Distributed Lag Boun...supporting
confidence: 91%
“…The aftereffect of the examination likewise uncovered that between bank loaning rate had a noteworthy negative association with market returns while the outcome for the remainder of different factors were conflicting inside the period considered. Sukruoglu and Nalin (2014) studied the role and effects of macroeconomic variables on stock market development in selected European countries using panel data from 1995 to 2011. The study found evidence that monetization and inflation had negative effects on stock market development while income, liquidity ratio, saving rate exerted positive influence on stock market development.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Other potentially significant macroeconomic drivers of stock market development include inflation [17] [21] and interest rates [18]. However, Şükrüoğlu and Nalin [22] show that inflation has significant negative effects on stock market development, while Kemboi and Tarus [20] show that macroeconomic stability does not play any significant role in generating gains in terms of economic growth. On the other hand, Evrim-Mandaci, Aktan, Kurt-Gumus, and Tvaronaviciene [23] provide evidence that foreign direct investment and worker's remittances also have a positive impact on stock market development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To evaluate the impact of macroeconomic instability on stock market development, this paper uses inflation, INF. Like Şükrüoğlu and Nalin [22], consumer price index is also used to proxy inflation in this paper.…”
Section: Model Specification and Data Measurementmentioning
confidence: 99%